Chemotherapy of Breast Cancer Cells Using Novel pH-ResponsiveCellulose-Based Nanocomposites - Mojtaba Abbasian; Farideh Mahmoodzadeh; Azra khalili; Roya Salehi (Tabriz University of Medical Sciences, 2019)
Purpose: The objective of the current study was to compare the anticancer efficacy ofdoxorubicin-loaded cellulose based magnetic (Fe3O4), zinc oxide (ZnO) nanoparticles on andfree doxorubicin (DOX) on MCF-7 breast cancer cells.Methods: Novel pH-sensitive cellulose-graft poly acrylic acid based Fe3O4 (Cellulose-g-PAAg-PAcMNPs) and ZnO (Cellulose-g-PAA-g-PAcZnO) nanocomposites were synthesized viapolymerization of acrylic acid and modified 3-(trimethoxysilyl) propyl methacrylate onto thecellulosic backbone via reversible addition-fragmentation chain transfer (RAFT) method.Results: Cellulose-g-PAA-g-PAcMNPs and Cellulose-g-PAA-g-PAcZnO nanocarriers with meandiameter of 15 and 38 nm were prepared successfully. DOX was loaded effectively to theZnO and Fe3O4 nanocarriers via complexing and electrostatic force with great encapsulationefficiency of 99.07% and 98.92%, respectively. DOX-loaded nanocarriers showed obvious pHdependenttumor specific drug release pattern. MTT assay results indicated that IC50 of theDOX loaded Cellulose-g-PAA-g-PAcZnO, DOX loaded Cellulose-g-PAA-g-PAcMNPs and freeDOX after 48 hours treatment with MCF7 cell lines were about 24.03, 49.27 and 99.76 μg mL−1,respectively. Therefore both DOX nanoformulations significantly increase antitumor abilitycompared to free DOX (P < 0.05). The results of MTT assay and DAPI staining revealed thatDOX-loaded Cellulose-g-PAA-g-PAcZnO NPs show higher chemotherapy efficiency in MCF7breast cancer cell line compare to the DOX-loaded Cellulose-g-PAA-g-PAcMNPs due to highinteraction of ZnO with DOX.Conclusion: The formation of the complexes between the DOX and ZnO nanoparticles atthe chelating sites of the quinone and the phenolic oxygen molecules of DOX, lead to moresustained drug release and enhanced chemotherapy effectiveness by increasing the intracellularconcentration of DOX.